Recurrent NFIA K125E substitution represents a loss-of-function allele: Sensitive in vitro and in vivo assays for nontruncating alleles. - Uehara, T.; Sanuki, R.; Ogura, Y.; Yokoyama, A.; Yoshida, T.; Futagawa, H.; Yoshihashi, H.; Yamada, M.; Suzuki, H.; Takenouchi, T.; Matsubara, K.; Hirata, H.; et al. (American journal of medical genetics. Part A, 2021)
Nuclear factor I A (NFIA) is a transcription factor that belongs to the NFI family. Truncating variants or intragenic deletion of the NFIA gene are known to cause the human neurodevelopmental disorder known as NFIA-related disorder, but no patient heterozygous for a missense mutation has been reported. Here, we document two unrelated patients with typical phenotypic features of the NFIA-related disorder who shared a missense variant p.Lys125Glu (K125E) in the NFIA gene. Patient 1 was a 6-year-old female with global developmental delay, corpus callosum anomaly, macrocephaly, and dysmorphic facial features. Patient 2 was a 14-month-old male with corpus callosum anomaly and macrocephaly. By using Drosophila and zebrafish models, we functionally evaluated the effect of the K125E substitution. Ectopic expression of wild-type human NFIA in Drosophila caused developmental defects such as eye malformation and premature death, while that of human NFIA K125E variant allele did not. nfia-deficient zebrafish embryos showed defects of midline-crossing axons in the midbrain/hindbrain boundary. This impairment of commissural neurons was rescued by expression of wild-type human NFIA, but not by that of mutant variant harboring K125E substitution. In accordance with these in vivo functional analyses, we showed that the K125E mutation impaired the transcriptional regulation of HES1 promoter in cultured cells. Taken together, we concluded that the K125E variant in the NFIA gene is a loss-of-function mutation.